Hepatitis B virus surface antibody titers in babies administered hepatitis B immune globulin both intravenously and intramuscularly after birth. (17th June 2016) - Hanaoka, Masachi; Hisano, Michi; Hama, Ikuko; Tsukamoto, Keiko; Ito, Reiko; Ito, Yushi; Sago, Haruhiko; Matsui, Akira; Yamaguchi, Koushi
Abstract: Objective : High rates of vertical transmission of hepatitis B virus (HBV) infection from carrier mothers to their babies are observed in hepatitis B e antigen (HBeAg)-positive mothers under the existing protocol. The current status suggests that the existing protocol may be insufficient for the prevention of mother-to-child transmission (MTCT) in HBeAg-positive mothers. To achieve complete prevention of HBV vertical transmission, we designed a protocol implementing intravenous administration along with ordinary intramuscular administration of HBV immune globulin (HBIG) to the baby after birth. Methods : We compared the HBV surface antibody (HBsAb) titer in babies who were simultaneously administered HBIG both intravenously and intramuscularly after birth with that in babies who received HBIG only intramuscularly. Results : The HBsAb titer rose rapidly after administration in the combined administration group, and the elevated titer was maintained for approximately 2 months. Although the antibody titer at the peak was nearly 6 times greater in the combined administration group than in the intramuscular administration group, the combined administration of HBIG did not have any effect on total IgG antibody levels in the bloodstream. Conclusion : The combined protocol was demonstrated to be safe and superior to the protocol of only intramuscular HBIG administration with respect to rapid elevation of HBsAb in the bloodstream. It could be an effective method for the prevention of MTCT in HBeAg-positive mothers.